Simplified hybrid control strategy for stand-alone DC microgrid with photovoltaic system to extend battery lifespan - Yan, Hein Wai (2021)
Conventionally, a flexible photovoltaic (PV) power control strategy is used to reduce battery utilization in stand-alone dc microgrids (dcMGs). However, conventional control schemes deploy multiple voltage controllers to regulate the dc-link voltage, causing mode transitions during the transients and complicating the controller design. This paper proposes a simplified control strategy for the PV system and the battery energy storage system in a stand-alone dcMG with a single voltage controller to regulate the dc-link voltage. The proposed control strategy enhances the transient response of the system by eliminating the mode transitions between voltage controllers and simplifying the hybrid control scheme while reducing the battery utilization. Additionally, the proposed solution does not require the knowledge of the load, which facilitates its application. The effectiveness of the proposed control strategy is validated with simulation results.